Pertanggung Jawaban Pidana dalam Kecelakaan Pesawat Udara Sipil di Indonesia - Safitri, Ira; Sudarto, Sudarto (FOCUS, 2025)
Aircraft accidents are events that can have a major impact on aviation safety and legal aspects. This research examines criminal liability in civil aircraft accidents in Indonesia, focusing on legal analysis from both international and national perspectives. This research aims to explore the application of criminal law against perpetrators of accidents caused by negligence, especially pilots in cases of human error. Based on the analysis of applicable regulations, such as the Criminal Code, Aviation Law Number 1 Year 2009, and international provisions in the 1944 Chicago Convention and Annex 13, it can be concluded that aircraft accidents caused by pilot negligence can lead to criminal liability, with sanctions in accordance with existing provisions. This research also identifies challenges in the implementation of legal provisions, as well as the importance of improving aviation safety through stricter regulations and transparent investigations.